2017
DOI: 10.1007/s13201-017-0572-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metal contamination in the sediment of the River Ghaghara, a major tributary of the River Ganga in Northern India

Abstract: The present study includes a systematic analysis of sediment contamination by heavy metals of the River Ghaghara flowing through the Uttar Pradesh and Bihar in Indian Territory. To estimate the geochemical environment of the river, seven heavy metals, namely Co, Cu, Cr, Ni, Cd, Zn, and Pb were examined from the freshly deposited river bed sediment. All the sediment samples were collected on a seasonal basis for the assessment of fluctuation in 2014-2015 and after preparation samples were analyzed using standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(72 citation statements)
references
References 48 publications
(50 reference statements)
3
61
1
Order By: Relevance
“…the release of some environmental pollutants such as heavy metals [4]. The discharge of wastewater from industrial effluent of manufacturing/processing companies, coal mine acid drainage, application of inorganic fertilizer, sludge from sewage and deposition of atmospheric pollutants have been reported to constitute the principal contributors of heavy metals found in sediments and water columns of rivers [2,5,6].…”
Section: Sediments and Water Column Contamination By Heavy Metals In mentioning
confidence: 99%
See 2 more Smart Citations
“…the release of some environmental pollutants such as heavy metals [4]. The discharge of wastewater from industrial effluent of manufacturing/processing companies, coal mine acid drainage, application of inorganic fertilizer, sludge from sewage and deposition of atmospheric pollutants have been reported to constitute the principal contributors of heavy metals found in sediments and water columns of rivers [2,5,6].…”
Section: Sediments and Water Column Contamination By Heavy Metals In mentioning
confidence: 99%
“…The extent of heavy metal contamination of the sediments of rivers can be evaluated employing several methods such as enrichment factor, index of geo-accumulation, metal contamination factor and the associated contamination degree and pollution index load [2,3,14,15]. Reviewed literature shows that the ecological risk assessment of the sediments due to heavy metal pollution can be evaluated via estimation of biological impairment using sediment quality guidelines (SQGs) [16].…”
Section: Sediments and Water Column Contamination By Heavy Metals In mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, El-Naggar et al (2000) reported that the circulation of heavy metals in the aquatic environment relies upon the physico-chemical characteristics of the aqueous phase and the accessibility of both inorganic and organic complexing agents. Singh et al (2017) stated that the physico-chemical properties of water conditions vary from season to season.…”
Section: Heavy Metals In Watermentioning
confidence: 99%
“…Ibrahim et al (2000) and Ibrahim and El-Naggar (2006) observed an obvious correlation between heavy metals concentrations in aquatic organisms and sediments. Moreover, Singh et al (2017) indicated that heavy metals can fix in sediment for brief periods then, small amount of these fixed heavy metals will enter the overlying water body again and uptake by the aquatic biota.…”
Section: Heavy Metals In Fishmentioning
confidence: 99%